The Prague Linguistic Circle and Dialectics (ENTHYMEMA, 2017)
The study deals with dialectics in the context of the Prague Linguistic Circle, particularly in the context of Jan Mukařovský’s thinking. The essay presents 1) main sources of Mukařovský’s dialectics, and outlines 2) Mukařovský’s dialectical method. The notion of dialectics appears in Mukařovský’s scholarly work in a set of connections. He applied dialectics as a method, manner or form of rationality. It served as a means of gaining knowledge about the world, specific phenomena and objects, their essence, interconnectedness as well as development. Mukařovský also used it as a procedure for resolving contradictions (antinomies) that he encountered in his scientific explorations and in ordinary practical activities. He understood dialectical thinking as dynamic, open, and pluralist thinking striving to reflect reality as a constant process. Gradual coming together of dialectics and materialism, evident in Mukařovský’s scholarly works from the mid-1930s, resulted, ten years later, in a public adoption of dialectical materialism.
Keywords: The Prague Linguistic Circle; Jan Mukařovský; Structuralism; Structural Poetics; Dialectics